2019
DOI: 10.1101/2019.12.21.885723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple merger genealogies in outbreaks ofMycobacterium tuberculosis

Abstract: The Kingman coalescent and its developments are often considered among the most important advances in population genetics of the last decades. Demographic inference based on the coalescent theory has been used to reconstruct the population dynamics and evolutionary history of several species, including Mycobacterium tuberculosis (MTB), an important human pathogen causing tuberculosis. One key assumption of Kingman's coalescent is that the number of descendants of different individuals does not vary strongly, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…It is also the first time multiple merger coalescent models based on neutral evolution and selection are contrasted. Previously, two neutral Λ-coalescents have been compared to data of outbreaks of the tuberculosis bacterium and used the Bolthausen-Sznitman coalescent ( α = 1) to model rapid selection (Menardo et al, 2019) Our findings have repercussions for and give impetus to further theoretical development of multiple merger coalescents, particularly for multiple merger coalescent models of strong selection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is also the first time multiple merger coalescent models based on neutral evolution and selection are contrasted. Previously, two neutral Λ-coalescents have been compared to data of outbreaks of the tuberculosis bacterium and used the Bolthausen-Sznitman coalescent ( α = 1) to model rapid selection (Menardo et al, 2019) Our findings have repercussions for and give impetus to further theoretical development of multiple merger coalescents, particularly for multiple merger coalescent models of strong selection.…”
Section: Discussionmentioning
confidence: 94%
“…This mode of reproduction characterizes many annual plants, a myriad of insects, and vertebrates such as the Pacific salmon ( Oncorhynchus ) and the Arctic cod ( Boreogadus saida ), a close relative of the Atlantic cod. We further posit that sweepstakes may be the mode of reproduction of viruses (Timm and Yin, 2012) as inferred from overdispersion of offspring distribution from superspreader individuals and events (Endo et al, 2020), some cancer cells (Kato et al, 2017), and various bacteria (Wright and Vetsigian, 2019; Menardo et al, 2019; Ypma et al, 2013). Fungi and plant pathogens, which cause extensive crop losses of great economic importance (Pimentel et al, 2000), may also reproduce by sweepstakes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that non-neutral processes confound demographic inference and should not simply be assumed away. Recombination (Hedge and Wilson, 2014), population structure (Heller et al, 2013), sampling design, gene conversion, and selection (Lapierre et al, 2016), as well as the skewness of reproductive success (Menardo et al, 2021a) all create spurious signs of population size changes. As observed by Lapierre et al, 2016, such methodological biases might explain why population size trajectories look suspiciously similar for a wide range of species.…”
Section: Bayesian Skyline Plots and The Issue Of Storytellingmentioning
confidence: 99%
“…Recently, progeny skew was brought up as a neglected aspect of MTBC evolution with potentially significant effects on genetic diversity (Morales-Arce et al, 2020) and population genetic inference (Menardo et al, 2021a). Progeny skew refers to the unequal distribution of offspring among parental individuals in a population.…”
Section: Bayesian Skyline Plots and The Issue Of Storytellingmentioning
confidence: 99%
“…forces that all reduce the observed genetic diversity present) result in an underestimation of MTBC mutation rates within-host when using evolutionary frameworks centered around the Wright–Fisher model. Use of evolutionary models that take clonality and skewed progeny distributions into account, such as multiple-merger coalescent theory (Menardo, Gagneux and Freund 2020 ; Morales‐Arce et al . 2020 ), may allow for a better estimate of MTBC genetic diversity production, including testing whether different MTBC genetic backgrounds indeed have different mutation rates.…”
Section: Introductionmentioning
confidence: 99%